Biological effects of whole Z. Officinale extract on chronic myeloid leukemia cell line K562 - KILINÇ, OLCA; ORUN, OYA; MEGA TİBER, PINAR; KOÇYİĞİT SEVİNÇ, SEVGİ (ELSEVIER SCIENCE BV, 2019)
The anticancer activity of Zingiber officinalis (ginger) is an area of active research. However, data is quite limited regarding its action and mechanism, especially in hematologic cancer types. Here, antiproliferative and apoptotic effects of whole extract of the rhizome of Zingiber officinalis (ZOWE), was investigated in K562 cell line derived from a chronic myeloid leukemia (CML) patient. Various concentrations of whole extract (0, 10, 25, 50 and 100 mu M) were tested in K562 cultures. Cytotoxicity and apoptosis was assessed with appropriate methods, as well as cellular ROS levels. In this study, we showed that ZOWE inhibited proliferation of K562 cells substantially, when compared to peripheral blood mononuclear cells (PBMCs) isolated from healthy donor. Increased Bax/Bcl-2 ratio, reduced mitochondrial membrane potential and increased PARP cleavage demonstrated that ZOWE inhibited proliferation by induction of apoptosis. These changes were coupled with an increase of reactive oxygen species (ROS) production. Furthermore, ZOWE addition to the culture also reduced expression levels of survival proteins pAkt and survivin, in a concentration dependent manner. Our results clearly mark that ZOWE causes to a reduction in cell viability, an induction of apoptosis and elevation in ROS levels in chronic myeloid leukemia cells and effects are significantly different from healthy peripheral blood mononuclear cells, further supporting its potential therapeutic value.
Keywords: Z.officinale; Peripheral blood mononuclear cells; Apoptosis; K562; Proliferation; ROS; 6-SHOGAOL INDUCES APOPTOSIS; BAD PHOSPHORYLATION; CANCER CELLS; INHIBITS PROLIFERATION; CYCLE ARREST; ACTIVATION; GINGER; 10-GINGEROL; CONSTITUENT; INDUCTION